TEACHING WRITING NARRATIVE PARAGRAPH THROUGH STIMULI QUESTION TECHNIQUE TO THE TENTH GRADE STUDENTS OF STATE HIGH SCHOOL 1 OF PALEMBANG - Magdad Hatim; Noviati Noviati; Heni Kurnia (Universitas PGRI Palembang, 2020)
The main problem of this research was “Is it effective to teach writing narrative through stimuli questions technique to the tenth-grade students of State High School 1 of Palembang?”. Therefore, the main objective of this research was to find out whether or not it was effective teaching writing narrative paragraphs through the stimuli question technique to the tenth-grade students of State High School 1 of Palembang. The method of this research was the experimental method. The population of this study was the tenth-grade students of State High School 1 of Palembang, in the academic year of 2016/2017. The sample of this study was 39 students who were chosen by convenience sampling. The data were collected through two kinds of tests, pre-test, and post-test. The data were analyzed by a matched t-test. Based on the results of the data analysis, it was found that the students’ average score in the pre-test was 59.1, and the students’ average score in the post-test was 68.6. Based on the matched t-test calculation, it was found out that the t-obtained was 8.84. the critical value of a 5% significance level was 1.684. it showed that t-obtained was higher than the t-table. From this study, it was found that teaching writing narrative paragraphs through stimuli questions technique to the tenth-grade students of State High School 1 of Palembang was effective.